Narratives from women studies family - Devaki Jain Ed (Sage Publications, 2003)
This unique volume brings together the personal accounts of 17 scholars and activists who have initiated and/or nurtured centres for women's studies. The heterogeneous group represented here covers the entire range of the women's studies family in India. The contributors highlight the inroads that women's studies has made to the knowledge base in the social and material sciences and where it has inspired a shift in policy or a change in curriculum.